Learning about ocean currents one track at a time. (31st March 2021) - Curran, Mary Carla; Ramsey, Andrée L.; Bower, Amy S.
Abstract: Oceans play an important role in weather and climate through transfers of heat and moisture to the atmosphere, and by moving heat and climate-relevant molecules like carbon dioxide around the globe. Energy also transfers from the atmosphere to the surface of the ocean, traveling down through the water column creating ocean currents that transport water with different temperatures, nutrients, and organisms from one part of the ocean to another. Students may not have known that there are ocean currents below the sea surface, but we provide methodology for sharing this information in a way that is accessible, including for the visually impaired. In addition to the Next Generation Science Standards (NGSS), Ocean Literacy Principles and The Essential Principles of Climate Literacy are addressed.